QFD method application in the process of hotel service quality improvement - Milunović Koprivica, Sandra; Bešić, Cariša; Ristić, Olga (Hotel and Tourism Management, 2019)
QFD method has been applied mainly in industrial companies. The service is intangible product that has its own specificities, and the market of hotel services in our country is becoming saturated. The aim of this paper is the identification of the most important quality characteristics (technical characteristics) of the hotel service and the direction of the hotel management activities to those characteristics that can be related to the highest number of stated customer requirements. Therefore, the result of the research is to define the key characteristics of the service quality and key activities in the design of the service that lead to customer satisfaction and achieving a competitive advantage in the market. Considering the results of the previous QFD method research, especially in the domain of this type of services, and especially in our country, one might say that even a small contribution to this matter is visible and could give impetus, not only for further research in this field, but also for the concrete application of the obtained solutions.